ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA SEGITIGA BERDASARKAN PROSEDUR NEWMAN - Irianti, Nathasa Pramudita; Setiawan, Rudy; Jaya, Felisita Casandra (Universitas Insan Budi Utomo, 2022)
The purpose of this study was to identify the types of errors based on Newman's procedure performed by seventh grade students of SMP Sunan Giri Malang in solving triangle story problems. The types of errors that are indicators of Newman's procedure are reading error, Comprehension errors, transformation errors, process skill errors, and the Encoding errors. This research belongs to the type of descriptive qualitative research with data collection carried out through tests, interviews, observations, and documentation with 10 students as research subjects. The results of this study indicate that the subject made errors (1) Reading errors, the subject does not understand the sentences they read, (2) Comprehension errors, the subject of writing is known and asked exactly like the question and does it carelessly. (3) Transformation errors, forget the triangle formula. (4) Process skill errors, the subject is wrong in the process of calculating multiplication, division and addition. (5) Encoding errors, the subject incorrectly wrote the final answer and did not write the final conclusion